Nest predation, brood parasitism and the reproductive success of the masked laughingthrush Garrulax perspicillatus in the rural habitat of central China. Issue 2 (May 2022) - Guo, Weibin; Lin, Buge; Hu, Zhiqing; Tan, Shudan; Tian, Jiaying; Wang, Changcao
Knowledge of nest site selection and reproductive ecology is fundamental to understanding the evolution of life history traits and developing species conservation strategies. However, life history traits of species in the genus Garrulax are poorly known. Particularly, research on the breeding biology of Garrulax perspicillatus in their natural habitat and comparison between populations in different environments (rural vs urban) are lacking. We presented data of nest site selection and breeding ecology of Masked Laughingthrush in central China during 2021, and made a detailed investigation on nest predation and interspecific brood parasitism. The breeding season began from March and ended in August. Most nests were built on Sulphur Bamboo ( Phyllostachys sulphurea ). First egg laying occurred between late March and late July. Incubation period lasted 13.9 days (±0.3 SE; 13–15) and nestling period of 13.1 days (±0.2 SE; 12–15). Average clutch size was 3.8 eggs (±0.1 SE; 3–7), and brood size at fledging was 2.7 young (±0.2 SE; 1–4). Overall, 36.2% of nesting attempts successfully fledged at least one young. Nest predation (0% in March, 38.2% in April, 30.0% in May, 20.0% in June and 27.3% in July) and interspecific brood parasitism (13.3% in May, 40.0% in June and 36.4% in July) were two main reasons for nest failure. This is the first study that provided detailed information of breeding ecology of Masked Laughingthrush in rural habitat, and we discussed the difference of life history traits between urban and rural habitats.